Teco: brinquedo inclusivo para crianças com deficiência visual - Santos, Aline Darc Piculo dos [UNESP] (Universidade Estadual Paulista (Unesp), 2016)
This project consists in a development of an inclusive toy for children with visual impairment. The toy was designed thinking of meet characteristics and specific needs of visually impaired children, yet not excluding full sighted children. For that, studies were done about the target audience, types of recommended materials, safety norms for toys, inclusive design and toy design through searches in the literature and interview with experts. The choice of this subject occurred because of the need and the gap for inclusive toys in the market. The Brazilian toy market is a growing sector, although not very explored yet. Besides that, toys for impaired children are mostly adaptations of traditional toys and do not have an appealing aesthetics for other children, which makes them excluding. The Teco toy aims to attract all the children between 3 and 6 years-old, independent on their visual degree, proportioning the inclusion and interaction

Este projeto consiste no desenvolvimento de um brinquedo inclusivo para crianças com deficiência visual. O brinquedo foi projetado pensando em atender as características e necessidades específicas das crianças com deficiência visual, não excluindo porém as crianças com visão total. Para isso, foram realizados estudos acerca do público alvo, tipos de materiais recomendados, normas de segurança para brinquedos, design inclusivo e design de brinquedos através de buscas bibliográficas e entrevista com especialistas da área. A escolha deste tema ocorreu tendo em vista a necessidade e a falta de brinquedos inclusivos no mercado. O mercado brasileiro de brinquedos é um setor em crescimento, porém ainda pouco explorado. Além disso, brinquedos para crianças com deficiência em sua maioria são adaptações de brinquedos tradicionais ou não apresentam uma estética atraente para as demais crianças, o que os tornam excludentes. O brinquedo Teco visa atrair todas as crianças na faixa etária de 3 a 6 anos, independente do grau de visão que possuem, proporcionando a inclusão e a interação
Keywords: Design centrado no usuário; Distúrbios da visão nas crianças; Brinquedos; Toys